1987
DOI: 10.1111/j.1432-1033.1987.tb13593.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by insulin and glucagon of noradrenaline-induced activation of isolated brown adipocytes from the rat

Abstract: 1. The effects of insulin (2 nM and 4 nM) upon oxygen consumption ( VoJ, lipolysis rates and indirectly derived rates of fatty acid utilization, by isolated brown adipocytes from warm-acclimated (W cells) and cold-acclimated (C cells) animals, induced by noradrenaline and glucagon separately and conjointly, are reported.2. Changes in interrelationships (coupling) between the parameters under different treatment regimes were assessed using bivariate regression analyses.3. Administration of glucagon with noradre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The increase of BAT weight did not differ between ICE and CA, although the increases in fat-free dry matter fraction and glucagon level of BAT were smaller in ICE than in CA. A possible role of glucagon in metabolic cold acclimation has been recently reported from our laboratory (KuROsHIMA et al, 1978(KuROsHIMA et al, , 1984(KuROsHIMA et al, , 1988 and also others (BILLINGTON et al, 1987;HOWLAND and BOND, 1987). The present study confirmed the previous results that glucagon level was higher in BAT from CA even in the resting state (HABARA and KUROSHIMA, 1983;, suggesting that glucagon exerts its thermogenic effect on BAT in high concentration.…”
Section: Discussionsupporting
confidence: 93%
“…The increase of BAT weight did not differ between ICE and CA, although the increases in fat-free dry matter fraction and glucagon level of BAT were smaller in ICE than in CA. A possible role of glucagon in metabolic cold acclimation has been recently reported from our laboratory (KuROsHIMA et al, 1978(KuROsHIMA et al, , 1984(KuROsHIMA et al, , 1988 and also others (BILLINGTON et al, 1987;HOWLAND and BOND, 1987). The present study confirmed the previous results that glucagon level was higher in BAT from CA even in the resting state (HABARA and KUROSHIMA, 1983;, suggesting that glucagon exerts its thermogenic effect on BAT in high concentration.…”
Section: Discussionsupporting
confidence: 93%
“…BAT is the main effector of NST and is regulated mainly by sympathetic noradrenaline [33]. In vitro and in vivo experiments have shown that BAT function is also regulated by different hormonal factors such as thyroidal, adrenocortical and pancreatic hormones [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In control rats maintained at room temperature (28 ± 2°C) the BAT histamine content was 23.4 ± 5.9 (mean ± SD) Homeothermic animals have the capacity to maintain body temperature by a variety of physiological responses, the most important of which is to enhance nonshivering thermogenesis (NST). The rapid growth of the brown adipose tissue (BAT) appears to play a crucial role in NST and is thought to be mainly regulated by sympathetic noradrenaline (Rothwell & Stock 1985, Géloën et al 1992 as well as other hormonal factors like thyroidal, adrenocortical and pancreatic hormones (Kuroshima et al 1984, Howland & Bond 1987.…”
Section: Cold Acclimatization (4-5°c) Is Accompanied By 2-3 Fold Incrmentioning
confidence: 99%
“…The rapid growth of the brown adipose tissue (BAT) appears to play a crucial role in NST and is thought to be mainly regulated by sympathetic noradrenaline (Rothwell & Stock 1985, Géloën et al 1992 as well as other hormonal factors like thyroidal, adrenocortical and pancreatic hormones (Kuroshima et al 1984, Howland & Bond 1987.…”
mentioning
confidence: 99%
See 1 more Smart Citation